Warpage-optimized polymer powder

CN115943065BActive Publication Date: 2026-10-27EOS GMBH ELECTRO OPTICAL SYST
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN201980074529.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-11-12
Filing Date
2019-11-07
Publication Date
2026-10-27
Estimated Expiration
2039-11-07

AI Technical Summary

Benefits of technology

[0017]根据本发明的粉末在增材制造方法以及由其制造的三维物体中具有出人意料的优点。因此,可以明显减少已知的混入干混物形式的粉末中的添加剂对于激光烧结方法的不利影响。结果,还明显减少了对于部件品质的不利影响。总之,所以,在工艺窗,层的z结合和/或部件的扭曲率方面获得了明显改进。这使得用NIR范围的光源进行激光烧结方法成为可能,而对于制造方法和/或所制造的三维物体没有任何不利影响。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003061737850000161
    Figure BDA0003061737850000161
  • Figure BDA0003061737850000171
    Figure BDA0003061737850000171
  • Figure BDA0003061737850000181
    Figure BDA0003061737850000181
Patent Text Reader

Abstract

Plastic powder for use as a building material for additive manufacturing of a three-dimensional object: at positions corresponding to cross-sections of the three-dimensional object in respective layers, in particular by selective solidification of the building material by action of radiation, wherein the plastic powder comprises a mixture of polymer-based particles and microparticulate additive particles, and wherein the microparticulate additive is selected such that the crystallization point of the mixture of polymer-based particles and microparticulate additive is essentially not increased compared to the crystallization point of the mixture of the polymer-based particles without the microparticulate additive.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention relates to a plastic powder (i.e., polymer powder) used in a method for manufacturing three-dimensional objects in a layer-by-layer manner, wherein selective regions of corresponding powder layers are melted and re-solidified. Another object of the invention is to provide a method for manufacturing three-dimensional objects using the plastic powder according to the invention as a building material, three-dimensional objects manufactured from the powder according to the invention, and a system for manufacturing three-dimensional objects according to the invention.

[0002] As known, for example, from DE 4410046, a method for manufacturing three-dimensional objects can be carried out layer by layer by using an electromagnetic radiation source and selectively sintering with electromagnetic radiation. In such a method, the three-dimensional object is manufactured layer by layer according to the principle of "additive manufacturing" by applying powder layers and selectively melting and solidifying the powder at locations corresponding to the cross-section of the object, thereby bonding these layers together.

[0003] Figure 1 An exemplary laser sintering apparatus is shown, by means of which a method for layer-by-layer fabrication of three-dimensional objects is performed. Figure 1 As can be seen, the device has a container 1. This container is open at the top and confined at the bottom by a carrier 4, for carrying the object 3 to be formed. A working plane 6 is defined by the upper edge 2 (or its respective sidewalls) of the container. The object is placed on the upper side of the carrier 4, and it is formed of a multi-layered powdered building material that is solidifiable by electromagnetic radiation and extends parallel to the upper side of the carrier 4. The carrier is movable in a vertical direction, i.e., parallel to the sidewalls of the container 1, by means of a height adjustment device. This allows adjustment of the position of the carrier 4 relative to the working plane 6.

[0004] An application device 10 is provided on the container 1 or the working plane 6 to apply the powder material 11 to be solidified onto the carrier surface 5 or the last solidified layer. Furthermore, an irradiation device in the form of a laser 7 is arranged on the working plane 6, emitting a guiding beam 8. This beam is deflected by a deflector 9, such as a rotating mirror, as a beam 8' deflected in the direction of the working plane 6. A control unit 40 is capable of controlling the carrier 4, the application device 10, and the deflector 9. Components 1-6, 10, and 11 are arranged in the frame 100.

[0005] During the fabrication of the three-dimensional object 3, powder material 11 is applied layer by layer to the carrier 4 or onto a previously solidified layer, and solidified by a laser beam 8' at the location corresponding to each powder layer of the object. After each selectively solidified layer, the carrier reduces the thickness of the next powder layer to be applied.

[0006] Compared to the systems described above, there are many modifications to methods and apparatuses that use electromagnetic radiation (which can also be used) for selective sintering to manufacture three-dimensional objects (molded bodies). For example, instead of lasers and / or beams, other systems can be used to selectively deliver electromagnetic radiation, such as mask exposure systems.

[0007] As a building material, powders containing thermoplastic polymer particles are frequently considered. The mechanical properties of the manufactured object can be influenced by appropriately selecting the polymer in the raw materials. For example, DE102008024281 A1 and DE 102008024288 A1 describe polymers that impart preferred mechanical properties to the final object. Similarly, it describes how mechanical properties can be further improved by using fillers. For example, carbon fibers, glass fibers, Kevlar fibers, carbon nanotubes, or fillers with low aspect ratios (glass beads, aluminum slag, etc.) or mineral fillers such as titanium dioxide can be introduced into powders containing polymers or copolymers.

[0008] To improve properties such as color or to introduce energy absorption for melting, additives, fillers, reinforcing fibers, and / or auxiliary materials can be incorporated into the polymer-based material prior to processing. For a polymer-based material to crystallize from the melt, crystal nuclei must be present; the crystallization rate is determined by factors such as nucleation density. / Müller, Kunststoff-Additive, 3rd edition, page 893 et ​​seq.).

[0009] A major, well-known drawback of adding additives is that it is typically accompanied by a reduced temperature window, poorer layer-to-layer bonding, and greater warpage (distortion) in 3D objects produced by methods operating on the principles of additive manufacturing. Functional additives, fillers, reinforcing materials, and / or auxiliary materials often act as additional nucleating agents, and as a result, typically increase the crystallization rate and therefore the analytically determined crystallization temperature. The crystallization temperature can be determined by the onset and extrapolated peak temperatures measured by DSC. An increase in the crystallization onset temperature leads to a reduction in the SLS sintering window (Manfred Schmid, “Selektives Lasersintern (SLS) mit Kunststoffen”, 2015, pp. 78 and 79) and a significant increase in the (built-in) warpage of laser-sintered 3D objects, which is attributed to an earlier onset of shrinkage effects.

[0010] This drawback becomes particularly pronounced in methods operating according to additive manufacturing principles, such as German patent application DE 102004012683 A1, when IR absorbers are added, for example, to melt and / or fuse plastics using electromagnetic radiation in the near-infrared (NIR) wavelength range. Because most polymers do not absorb NIR radiation, the additive acts as an NIR radiation absorber, absorbing the energy of the introduced wavelength and converting it into heat.

[0011] Therefore, one object of the present invention is to provide a method and system for manufacturing three-dimensional objects by selectively solidifying building materials through radiation at locations corresponding to the cross-sections of the three-dimensional object in a respective layer, which at least partially overcomes the aforementioned disadvantages. Another main object of the present invention is to provide a powder of building materials used in such an improved method, and a three-dimensional object manufactured by the advantageous method.

[0012] This objective is achieved by the plastic powder according to claim 1, the manufacturing method according to claim 10, the three-dimensional object according to claim 11, and the system according to claim 12. Further embodiments of the invention are set forth in the dependent claims.

[0013] According to a first aspect of the invention, the plastic powder comprises a mixture of polymer-based particles and particulate additives, wherein the particulate additives are selected such that the crystallization point of the mixture of polymer-based particles and particulate additives is substantially no increase compared to the crystallization point of a mixture containing the polymer-based particles but without the particulate additives. Preferably, the particulate additives comprise (preferably solid) particulate carbon materials, preferably graphite and / or carbon black and particularly gas black. Preferably, the particulate additives consist of carbon black and / or graphite, particularly gas black. Gas black refers to carbon black that can be obtained as a residue from the combustion of natural gas. Compared with other industrial carbon blacks, gas black has a lower carbon content (<98 wt%) and / or a narrower particle size distribution.

[0014] The particulate carbon material is selected such that the crystallization point of the mixture of the polymer-based particles and the particulate additive is substantially no higher or almost no higher than the crystallization point of the mixture of the polymer-based particles without the particulate additive. Specifically, the property of substantially no or almost no increase in the crystallization point is satisfied if the increase is no greater than 2.5°C, preferably no greater than 2.0°C, and in some embodiments no greater than 1.5°C. When measuring the increase in crystallization point, fluctuations in the measurement method, which are 0.5-1.0°C in the case of DSC, should be taken into account.

[0015] The powder according to the invention is specifically intended as a building material for manufacturing three-dimensional objects by selectively solidifying the building material, particularly NIR radiation, at locations corresponding to the cross-section of the three-dimensional object in a respective layer. The term "solidification" is understood as at least partially melting, followed by solidification or binding of the building material. In the context of solidification, the term "selective" refers to localized irradiation at locations of the continuous layer to be solidified, while ignoring locations of the layer not intended to solidify. The opposite of such selective solidification is, for example, a technique in which the building material is not spread across the entire layer, but only at the points where solidification is desired. In this case, irradiation may also be applied to areas not intended to solidify.

[0016] The term "three-dimensional object" is used herein synonymously with the term "molded body." The term "polymer particles" is used herein synonymously with the term "polymer-based particles," and refers herein to particles that contain the polymer described in more detail herein, preferably comprising at least 20% by weight, more preferably at least 40% by weight, and particularly at least 60% by weight. The remaining components may substantially comprise fillers.

[0017] The powder according to the invention offers unexpected advantages in additive manufacturing methods and the three-dimensional objects manufactured therefrom. Therefore, the adverse effects of additives known to be incorporated into dry-mix powders on laser sintering methods can be significantly reduced. Consequently, adverse effects on part quality are also significantly reduced. In summary, significant improvements are achieved in process window, layer z-bonding, and / or part torsion. This enables laser sintering using NIR-range light sources without any adverse effects on the manufacturing method and / or the manufactured three-dimensional objects.

[0018] A non-significant increase in the crystallization point here means that the increase in the crystallization point is specifically no greater than 2.0 °C. The crystallization point can be determined by measuring the temperature at which the mixture melt just begins to crystallize (Tc) in a DSC measurement. K开始 The crystallization point is therefore determined by ( ). K开始 The starting temperature can be determined using DSC (Differential Scanning Calorimetry). The corresponding DSC measurement for determining the starting temperature is preferably performed according to ISO 11357. A suitable instrument is, for example, the Mettler Toledo DSC 823.

[0019] The advantages and embodiments of the present invention are shown below.

[0020] In a preferred embodiment of the invention, the average primary particle diameter of the particulate additive is in the nanometer range. The term "nanometer range" refers to a size range of 1 nm to 999 nm. Preferably, the average primary particle diameter of the particulate additive is at most 500 nm, more preferably at most 250 nm, even more preferably at most 100 nm, and particularly at most 60 nm. In this way, an undesirable increase in the crystallization point of the mixture of the polymer-based particles and the particulate additive compared to the crystallization point of the mixture of the polymer-based particles without the particulate additive can be minimized or avoided.

[0021] The term "primary particle diameter," distinct from the diameter of aggregates or secondary particles, refers to the particle size of initial, unaggregated particles. This indicates that an aggregate consists of many primary particles, which represent the smallest indivisible unit of the aggregate. Primary particles can be obtained by processing a sample in an ultrasonic bath, starting from an aggregate. Preferably, the primary particle diameter refers to the average diameter. In this invention, the primary particle diameter can be determined according to ASTM D 3849, particularly via morphological characterization using transmission electron microscopy (TEM) according to ASTM D3849.

[0022] For determining the diameter of primary particles, a suitable instrument is, for example, a LEO 912Omega: 120kV TEM instrument equipped with a Proscan Slow Scan CCD 1024x1024 pixel camera and a 460-mesh copper grid with a carbon film. Image analysis can be performed using Olympus Soft Imaging Solutions “analySIS”. For sample preparation, 8 mg of sample can be dispersed in 1 mL of isopropanol in an ultrasonic bath for 5 min. Several drops can be taken from this and dispersed again in 1 mL of isopropanol in an ultrasonic bath for 5 min. Subsequently, a drop of the solution can be dropped onto the copper grid. Microscopic examination at different magnifications can be performed. Preferably, the examination can be performed at a microscope magnification of 2000x (including post-magnification with the camera, the magnification is 40000x). Optionally, calibration detection can be performed using a row-grid with a specified row spacing and / or a conformity test based on the TEM surface.

[0023] In a preferred embodiment of the invention, the particulate additive comprises or is composed of a particulate NIR absorber. This applies, for example, to solid particulate carbon materials, particularly carbon black and / or graphite. The term "NIR absorber" herein refers to a substance or mixture of substances that at least partially absorbs near-infrared (NIR) radiation. For readability, the following statements refer to the substance as an NIR absorber. This also applies if a mixture of substances is used as an NIR absorber. According to the invention, the NIR absorber may comprise carbon black, wherein preferably the NIR absorber is carbon black, and no other NIR absorber is present or is present only to a small extent. The term "to a small extent" means that the ratio of the absorption rate of carbon black to the absorption rate of other NIR absorbers in at least a portion of the NIR range is at least 2 or 3, preferably at least 4 or 5, more preferably at least 6 or 7, and more preferably at least 8 or 9 or at least 10. The NIR absorber preferably exhibits absorption at at least one of the following wavelengths: 980±10 nm and / or 940±10 nm and / or 810±10 nm and / or 640±10 nm.

[0024] Within the scope of this invention, other suitable additives can, in principle, be added to the dry blend to impart advantageous properties to the plastic powder or the three-dimensional objects made therefrom, or to utilize certain advantageous properties of such additives in the manufacturing process. However, to take full advantage of the invention, it is preferred that the dry blend contains at least one or more additives that reflect (proportionate to the weight and particle size used) up to 70%, 60%, or 50%, preferably up to 40%, 30%, or 20%, and particularly up to 15%, 10%, or 5% of NIR radiation. This allows the NIR radiation in the plastic powder to be used by the NIR absorber to generate heat, and does not reflect unused radiation. Because the energy delivered by a laser diode is significantly less than that of a conventional laser (e.g., such as a CO2 laser), the powder can be processed entirely in this manner, and energy savings can be considered an advantage.

[0025] From the above context, it is clear that in one embodiment of the invention, the plastic powder can well contain reflective particles having a surface that at least partially reflects NIR radiation. This approach allows, on the one hand, to take advantage of certain material-related benefits in the IR range, while simultaneously utilizing effects relevant to the present invention.

[0026] For example, the known white pigment titanium dioxide acts as such reflective particles. The use of titanium dioxide has unexpected advantages, especially in the context of this invention. These will be described below.

[0027] As stated at the outset, the object of this invention is to use NIR absorbers to increase the absorption rate within the NIR wavelength range (e.g., <1 μm). The inventors have discovered that carbon black possesses very high absorption capacity and the ability to efficiently convert absorbed energy into heat. In the case of commonly available materials, the amount of carbon black should be as small as possible to allow for the manufacture of parts that are as bright as possible. This makes the parts more suitable for subsequent coloring, particularly light colors.

[0028] In the case of plastics, the so-called natural color refers to a light white, brownish-brown natural product. When using natural-colored plastics mixed with carbon black, the inventors noticed that parts manufactured from them exhibited an uneven color impression. The parts displayed a "spotted" appearance.

[0029] Surprisingly, it has been found that if TiO2 is pre-mixed into naturally colored plastics, parts with a significantly more uniform color impression can be produced. Therefore, by adding titanium dioxide, parts with a uniform color can be obtained, even when using a small amount of carbon black. Therefore, the reflective particles preferably contain TiO2. Preferably, the reflective particles are formed substantially of TiO2.

[0030] Preferably, the weight percentage of the reflective particles relative to the total weight of the plastic powder is 0.5%-15.0%, preferably at least 0.5% and / or a maximum of 5%, particularly at least 0.5% and / or a maximum of 2%.

[0031] In a preferred embodiment of the invention, the plastic powder is in the form of a preferably homogeneous dry blend of polymer-based particles and particulate additives. In this preferred embodiment, the dry blend is a mixture of polymer-based particles and particulate additives, i.e., the additive particles have not yet been introduced into the polymer-based particles, for example, via polymer melt or by co-precipitation from solution or by any other means. The term "dry blend" is synonymous with the term "dry co-blending" and, according to the invention, refers to the mixture of polymer-based particles and particulate additive particles. Optionally, the dry blend may additionally contain one or more additional substances that may optionally be mixed in and / or completely or at least partially introduced into the polymer particles during a dry blending method.

[0032] Specifically, in this invention, a distribution is considered "uniform" if, in a plurality of random samples (e.g., 2, 3, 4, 5, 6, etc.), the minimum NIR absorber concentration deviates from the maximum NIR absorber concentration by less than 30%, preferably less than 20%, and more preferably less than 10%. Preferably, the samples are taken from a mixture of at least 1 g, more preferably at least 5 g. This preferably avoids spatially different absorption of NIR radiation. This increases the stability of the method, and the result is the production of three-dimensional objects with improved mechanical properties.

[0033] The powder according to the invention can be obtained by adjusting the prescribed weight proportions by mixing polymer-based particles with NIR absorber particles and, if necessary, additional additives in a mixing step at an appropriate mixing ratio. This mixing process is conveniently carried out in a one-step manner as follows:

[0034] (i) providing the polymer-based particles and NIR absorber particles; and

[0035] (ii) Dry-mix at least the polymer-based particles and NIR absorber particles.

[0036] For this purpose, a container mixer with a standard blade structure (one bottom cleaner and one dispersing blade (400 mm diameter)) from the Mixaco CM 150-D is suitable, which allows for two-stage mixing: 2 min at 516 rpm and 4 min at 1000 rpm.

[0037] However, the aforementioned hybrid procedure can also be performed in several hybrid steps (multi-level method):

[0038] (i) A first dry blend (so-called masterbatch) is provided by dry blending at least polymer-based particles and carbon black particles having a first proportion of carbon black particles.

[0039] (ii) Adding additional polymer-based particles to the first dry blend to obtain a second dry blend having a relatively lower proportion of carbon black particles than the second dry blend.

[0040] (iii) Optional additional separate addition steps: In each case, additional polymer-based particles are added to the second and optional additional dry mix to obtain a progressively decreasing proportion of carbon black particles in each case. Optionally, the dry mix may be sieved at least once, preferably through a 125 μm sieve, at least after at least one of steps (i) and (ii) and optional step (iii) and / or addition steps. A single-stage or multi-stage mixing method is performed, and the weight percentage of carbon black relative to the total weight of the polymer-based particles and carbon black particles is defined as being within a predetermined range after addition step (ii) or addition step (iii).

[0041] Surprisingly, it has been found that the uniformity of the single-stage method is superior to that of the multi-stage method. Therefore, the single-stage method is the preferred embodiment of both options. The present invention therefore does not favor providing the plastic powder via a masterbatch method, but rather favors providing the entire quantity of plastic powder in a single process step, i.e., in a single batch process. The advantages of the single-batch method, in addition to the more uniform distribution of the NIR absorber in the powder, include a particularly simpler and more cost-effective method, as only one step is required.

[0042] In a preferred embodiment of the invention, the particulate additive is gas black. Preferably, the average primary particle diameter of the gas black is 1-50 nm, more preferably at least 5 nm and / or a maximum of 47 nm, more preferably at least 10 nm and / or a maximum of 30 nm, and particularly at least 15 nm and / or a maximum of 25 nm.

[0043] Advantageously, the choice of such an average primary particle diameter improves method stability and / or molding quality. Furthermore, fluidization and / or coating quality, as well as constant coating behavior and / or a sufficiently large processing window, can be achieved. The processing window is defined as the temperature range between the crystallization temperature (TC) and the melting temperature (TM). Surprisingly, in the context of this invention, it has been found that the improvement relates to the average primary particle diameter, regardless of the degree or level of initial primary particle deagglomeration when mixed with polymer-based particles.

[0044] Coating quality is defined as a uniform, dense coating on the surface, without areas of significantly lower bulk density, regardless of whether the powder or pre-molten building material is beneath the coated powder layer. Consistent coating behavior refers to stable coating behavior, potentially lasting for hours, throughout the entire construction work period. Construction work refers to building work where the work involves editing positioned and parametric components in software.

[0045] In a preferred embodiment of the invention, the particulate additive has a weight percentage of 0.01%-5% relative to the total weight of the polymer-based particles and the particulate additive, preferably at least 0.02% and / or a maximum of 2%, more preferably a maximum of 1%, and even more preferably a maximum of 0.45%.

[0046] In a preferred embodiment of the invention, the polymer of the polymer-based particles is a thermoplastic and / or semi-crystalline polymer.

[0047] In principle, this invention is not limited to specific polymer-based plastics. Suitable polymer bases can be selected from homopolymers, copolymers, and polymer blends (also called polymer blends). A polymer blend (also called a "polymer blend") is understood to be a mixture of two or more different polymers. Polymer blends can be single-phase polymer blends (homogeneous polymer blends) or multi-phase polymer blends (heterogeneous polymer blends). In the case of multi-phase polymer blends, several glass transitions are typically observed using differential scanning calorimetry (DSC). Furthermore, in multi-phase polymer blends, multiple melting peaks corresponding to the melting points of the single phases can be observed using DSC.

[0048] The polymer may be selected from polyaryl ether ketone (PAEK), polyaryl ether sulfone (PAES), polyamide, polyester, polyether, polylactide (PLA), polyolefin, polystyrene, polyphenylene sulfide, polyvinylidene fluoride, polyphenylene ether, polyimide, polyetherimide, polycarbonate, and copolymers comprising at least one of the aforementioned polymers or their monomer units, and polymer blends of one or more of the aforementioned polymers or their copolymers, wherein the selection is not limited to the aforementioned polymers and their copolymers and polymer blends. The term "polymer" may also include oligomers having cyclic or ring-shaped molecular structures. An example of such oligomers is CBT (cyclic butylene terephthalate), used to prepare PBT (polybutylene terephthalate).

[0049] Suitable PAEK polymers and copolymers are selected, for example, from polyetheretherketone (PEEK), polyetherketoneketone (PEKK), polyetherketone (PEK), polyetheretherketoneketone (PEEKK), polyetherketoneketoneketone (PEEKK), polyetherketoneetherketoneketone (PEKEKK), polyaryletheretherketoneketone (PEEEK), and copolymers comprising at least one of the aforementioned polymers.

[0050] Suitable polyamide polymers or copolymers can be selected from polyamide 6 / 6T, and polyamide elastomers such as polyether block amides such as PEBAX. TM The base materials include polyamide 6, polyamide 66, polyamide 11, polyamide 12, polyamide 612, polyamide 610, polyamide 1010, polyamide 1012, polyamide 1212, polyamide PA 6T / 66, PA 4T / 46, and copolymers comprising at least one of the aforementioned polymers. Suitable polyester polymers or copolymers may be selected from polyalkylene terephthalates (e.g., PET, PBT) and their copolymers.

[0051] Suitable polyolefin polymers or copolymers may be selected from polyethylene and polypropylene. Suitable polystyrene polymers or copolymers may be selected from syndiotactic and isotactic polystyrene. Suitable polyimide polymers or copolymers may be selected from polyarylamides, polybismaleimides, and especially polyetherimides.

[0052] In a preferred embodiment of the invention, the polymer particles comprise at least one polymer selected from at least one of the following as the polymer material: polyaryletherketone (PAEK), polyarylethersulfone (PAES), polyamide, polyester, polyether, polylactide, polyolefin, polystyrene, polyphenylene sulfide, polyvinylidene fluoride, polyphenylene ether, polyimide, polyetherimide, polycarbonate, preferably selected from polyamide, more preferably selected from polyamide 12, polyamide 11 and / or polyamide 1012, and / or selected from at least one copolymer comprising at least one of the aforementioned polymers or their monomer units, and / or selected from at least one polymer blend comprising at least one of the said polymers or copolymers. Preferably, the polymer is a polyamide, more preferably polyamide 12, polyamide 11 and / or polyamide 1012.

[0053] In one embodiment of the invention, the polymer-based particles comprise a PAEK polymer, copolymer, or blend as the polymer material, a polyamide, or a polyetherimide, wherein the PAEK is preferably PEEK, PEKK, PEK, PEEKK, PEEKKK, and / or PEEEK, and the preferred polyamide is polyamide 12 and / or polyamide 11. Furthermore, molded articles made from these polymer materials meet the high requirements related to mechanical stress.

[0054] The present invention is also suitable for use in polymer blends.

[0055] If the polymer has the property of not absorbing or only slightly absorbing electromagnetic radiation in at least a portion of the NIR range, the particulate additive preferably comprises or is composed of a particulate IR absorber. As stated at the beginning, this applies to most polymers. The term "in a small extent" means that the absorption rate of the excess polymer-based particles is significantly less than that of the NIR absorber. For example, the ratio of the absorption rate of the NIR absorber to the absorption rate of the polymer-based particles in at least a portion of the NIR range (e.g., one or more wavelengths below: (980±7) nm and / or (940±7) nm and / or (810±7) nm and / or (640±7) nm) is at least 2 or 3, preferably at least 4 or 5, more preferably at least 6 or 7, and particularly at least 8 or 9 or at least 10.

[0056] Regarding the particle size of the polymer-based particles, there are no limitations beyond those typically found in the field of laser sintering. A suitable average particle size d50 is at least 10 μm, preferably at least 20 μm, particularly preferably at least 30 μm and / or a maximum of 150 μm, preferably a maximum of 100 μm or 90 μm, particularly preferably a maximum of 80 μm, and especially at least 40 and / or a maximum of 70 μm.

[0057] Another aspect of the present invention is a method for preparing a specific plastic powder according to the invention. In particular, the powder is used in methods for additive manufacturing of three-dimensional objects, especially at locations corresponding to the cross-section of the three-dimensional object in a respective layer, particularly by means of radiation, to selectively solidify powdered building materials. According to the invention, the method comprises at least the following steps:

[0058] (i) Provide the polymer-based particles.

[0059] (ii) Provide the microparticle additive particles, and

[0060] (iii) Dry-mix at least the polymer-based particles and the particulate additive particles.

[0061] Optionally, other additives such as TiO2 may be mixed with the polymer-based particles and particulate additive particles.

[0062] Optionally, after step (iii), the polymer powder can be packaged, preferably dehumidified.

[0063] In a preferred embodiment, the polymer-based particles are mixed with particulate additive particles and optionally additional additives in a one-step process at a desired mixing ratio to adjust the prescribed weight proportions. However, the mixing method can also be carried out in several mixing steps (multi-stage method) as described above. Again, as explained above, the uniformity of a single-stage method is superior to that of a multi-stage method.

[0064] In an advantageous embodiment, the mixture of the polymer and the particulate additive is homogeneous. Particularly good homogeneity is achieved by the one-step mixing method disclosed herein.

[0065] Another aspect of the invention is a molded body or three-dimensional object manufactured by selectively solidifying powdered building materials through radiation, preferably NIR radiation, at positions corresponding to the cross-sections of the three-dimensional object in the respective layers. NIR radiation is not absolutely necessary, but is preferred. In principle, the powder can also be processed by other layering manufacturing methods, and surprisingly, the same advantages are provided here.

[0066] Preferably, the molded body has at least one or two of the following features:

[0067] (a) A microscopically observable crystalline region in the form of spherules, with a spherule size of at least 20 μm.

[0068] (b) Manufacturing the torsion rate Δ(h) 中心 -h 左 )+Δ(h 中心 -h右 The thickness is less than 0.5mm, preferably less than 0.25mm, and more preferably less than 0.2mm.

[0069] To determine the torsion rate, a cube (e.g., with dimensions of 250mm x 6mm x 21mm) can be constructed. As a measure of the manufacturing torsion rate (the torsion rate during the manufacturing process), the difference in cube height between a measurement point at the edge and a measurement point at the center (in this embodiment: x = 125mm) is given as a percentage relative to the actual height at the center of the cube, where the height at the center is typically greater than that at the edge.

[0070] As a measure of cooling torsion rate (torsion rate after manufacturing process, which is not formed in defective material compared to manufacturing torsion rate), it indicates the curvature of the bottom side of the three-dimensional object at the middle of the three-dimensional object (in the embodiment: x = 125 mm), wherein the shape of the curved bottom side is approximated by parabolic mathematics.

[0071] Apply the following formula: f(x) = ax 2 And for non-twisted parts, a = 0.

[0072] The curvature of the graph is defined as

[0073] Therefore, at the center of the component corresponding to the vertex of the parabola, κ(0) = 2a applies.

[0074] In a preferred embodiment, the plastic powder according to the invention preferably serves as the building material.

[0075] The plastic powder according to the invention is suitable for conventional laser sintering methods using CO2 lasers, as well as methods based on short-wavelength radiation such as NIR radiation, and other additive manufacturing methods such as Multi JetFusion from HP. Surprisingly, the addition of the microparticle additive particles provides the same advantages in both methods.

[0076] By using the plastic powder according to the invention as a building material, in addition to the aforementioned advantages, the following effects are also produced, which also represent a preferred embodiment of the invention. Therefore, in a preferred embodiment, the molded body has at least one, preferably two or more, combinations thereof, and more preferably all of the properties defined below:

[0077] (i) The tensile strength is at least 40 MPa, preferably at least 48 MPa;

[0078] (ii) The Young's modulus is at least 1600 MPa; preferably at least 1700 MPa;

[0079] (iii) The elongation at break is at least 2.5%; preferably at least 3.0%.

[0080] Tensile strength, Young's modulus, and elongation at break were determined according to EN ISO 527 using specimens of type 1BB. The conditioning conditions have a relevant influence on the measurement results of mechanical properties such as tensile strength, Young's modulus, and elongation at break. The mechanical properties of the specimens were determined under dry conditions, wherein the test was conducted for a maximum of 3 hours after the parts were unpacked. According to ISO 291, a temperature of (23±2) °C and a relative humidity of (50±10)% are preferred test climatic conditions for determining mechanical properties. This test climatic condition should be maintained when determining mechanical properties. According to EN ISO 527-1, the test speed should be consistent between the parts of interest. A test speed of 50 mm / s is used.

[0081] To make the method more economical and environmentally friendly, the remaining uncured building material (“used powder”) from previous manufacturing cycles can be reused in subsequent cycles. For this purpose, the used powder is mixed with a new powder mixture (“new powder”) at a predetermined ratio. In a preferred embodiment, the building material thus comprises a proportion of used powder (which is left over as uncured building material during the manufacturing of the three-dimensional object) and a proportion of new powder (which was not previously used in the object manufacturing). Preferably, the proportion of the new powder is at most 70% by weight, particularly at most 60%, 50%, or even 40% by weight.

[0082] Another aspect of the invention provides a system for manufacturing three-dimensional objects, used to selectively solidify powdered building materials according to the invention by means of radiation, preferably NIR radiation, at positions corresponding to the cross-section of the three-dimensional object in a respective layer. According to the invention, the system comprises at least one radiation source designed to emit electromagnetic radiation, particularly at wavelengths or wavelength ranges specifically within NIR, a processing chamber designed as an open container with container walls, a carrier located within the processing chamber, wherein the processing chamber and the carrier are vertically movable relative to each other, a storage container, and a horizontally movable coating device. The storage container is at least partially filled with the plastic powder of the invention as a building material.

[0083] In a preferred embodiment of the invention, the electromagnetic radiation is specifically emitted within a window (λ2-λ1) of the NIR range not greater than 50 nm (λ2-λ1 ≤ 50 nm), preferably not greater than 40 nm, more preferably not greater than 30 nm, and particularly not greater than 20 nm (λ2-λ1). This allows the plastic powder according to the invention to contain additional substances that will interfere with a first sub-range of the NIR range, due to their absorption or reflection capabilities. By selecting a relatively narrow wavelength range outside the first sub-range, the interference effect can be reduced or prevented.

[0084] In a preferred embodiment, the radiation source is designed to emit electromagnetic radiation at wavelengths or wavelength ranges specifically located in a NIR (Non-Infrared Radiator). In a preferred embodiment of the invention, the radiation source emits electromagnetic radiation at one or more wavelengths specifically between 500 and 1500 nm, particularly at one or more of the following wavelengths: (980 ± 10) nm and / or (940 ± 10) nm and / or (810 ± 10) nm and / or (640 ± 10) nm. Preferably, the radiation source emits at (980 ± 10) nm and / or (940 ± 10) nm.

[0085] In a preferred embodiment of the invention, the radiation source comprises at least one laser, preferably one or more laser diodes. The laser diodes can be arranged in rows or staggered arrays. They can also be arranged in a 2D array. It can be an edge emitter. Preferably, it is a surface emitter (VCSEL or Philips-VCSEL). High build speeds can be achieved through linear exposure. Furthermore, using laser diodes allows for high efficiency and reduced energy costs.

[0086] For layer-by-layer melting of the polymer powder according to the present invention, appropriate methods or system parameters are selected. In addition to adjusting the proportion of NIR absorber, layer thickness, laser power and exposure speed, and laser wavelength are intentionally selected.

[0087] Suitable laser diodes typically operate at a power of 0.1-500 watts, preferably at least 1.0 watt and / or a maximum of 100 watts. The laser beam can be focused with a radius of 0.05 mm-1 mm, preferably at least 0.1 mm and / or a maximum of 0.4 mm. The exposure speed (i.e., the focusing speed of the laser relative to the construction plane) is typically 10 mm / s-10000 mm / s, preferably at least 300 mm / s and / or a maximum of 5000 mm / s.

[0088] In the context of this invention, the terms "comprising" or "containing" and their grammatical variations have the following meanings: In one embodiment, additional elements may be included in addition to those mentioned. In another embodiment, essentially only the mentioned elements are included. In other words, in addition to their conventional meanings, the terms may, in a particular embodiment, be synonymous with the terms "essentially composed of" or "consisting of".

[0089] Figure 1 An exemplary conventional laser sintering apparatus is shown for manufacturing three-dimensional objects layer by layer.

[0090] Figure 2 shows a magnified image of the cooled PA12 melt. Large spherical particles are visible.

[0091] Figure 3 PA12 and industrial carbon black (used) are shown. A magnified image of the cooled melt of a mixture (570 as an example). Many small spherical particles are visible.

[0092] Figure 4 The isotherms and conversion rates of DSC for mixtures of polymer particles and different types of carbon black are shown.

[0093] Figure 5 Showing by Figure 4 The DSC isotherm and the conversion rate determined by t 峰 [min] and t 1 / 2 The values ​​of [min] and α[%] conversion rate.

[0094] Figure 6 shows a magnified image of the cooled PA 12 melt. Large pellets are visible.

[0095] Figure 7 PA 12 and industrial carbon black (used) are shown. A magnified image of the cooled melt of a mixture (570 as an example). Many small spherical particles are visible.

[0096] Figure 8 shows a magnified image of the cooled melt of a mixture of PA 12 and gas black (using Spezialschwarz 4 as an example). The size of the pellets is comparable to that of the melts in Figures 2 and 7.

[0097] The following examples are for illustrative purposes and are not to be construed as limiting. They define other preferred embodiments of the invention. Example

[0098] Implementation Plan 1

[0099] Mixtures of polymer-based particles and different types of particulate additives were prepared. Different types of particulate carbon materials were tested as particulate additives, and the corresponding tests could be performed similarly with other particulate additives. The polymer-based particles were identical throughout the blends and, as a representative example, were manufactured using PA 2201. They exhibited high sphericity and d50 values ​​of 50-62 μm. PA 2201 was exemplarily used for PA 12-based polymer-based particles.

[0100] Various commercially available products containing industrial carbon black or graphite are used as types of particulate carbon materials. The following types are used:

[0101] - Air Black: Spezialschwarz 4, Spezialschwarz 5, Spezialschwarz 6.

[0102] -Lamp black: Flammruβ101, Monarch 570, Mogul L, Printex 200, Printex G, PrintexXE-2B; Ensaco 150P, Arosperse 15.

[0103] - Graphite: Timrex SFG 6 graphite.

[0104] Different manufacturing methods produce significantly different grain size distributions (KGV). Lamp black has a wide KGV, while fumed black has a narrow KGV. Fumed black typically has an oxidized surface.

[0105] The mixture was homogenized using a container mixer, specifically a Mixaco CM150-D model with a standard blade configuration: one bottom cleaner and one dispersing blade (400 mm in diameter). Two-stage mixing was performed at 516 rpm for 2 minutes and at 1000 rpm for 4 minutes, followed by DSC measurement. DSC measurements were conducted according to ISO 11357 using a Mettler Toledo DSC 823.

[0106] The crystallization temperature was then determined. The results are shown in Table 1 below.

[0107] Table 1: Crystallization temperatures of mixtures of polymer particles and different types of particulate carbon materials.

[0108]

[0109]

[0110] The results show that, in the test series, the mixture containing gas black had the lowest crystallization temperature. Since the mixtures differed only in the type of particulate carbon material, it can be concluded that gas black produced the lowest increase in crystallization temperature.

[0111] Implementation Plan 2

[0112] A mixture of polymer particles and different types of carbon black was prepared. The polymer particles were the same as those used in Embodiment 1. Different commercially available products containing industrial carbon black were used as the carbon black types. The differences in these characteristics were particularly in their particle size distribution.

[0113] The mixture was thoroughly mixed and subjected to the DSC measurement described in Example 1. The crystallization temperature was then determined. The results are shown in Table 2 below.

[0114] Table 2: Crystallization temperatures of mixtures of polymer particles and different types of carbon black.

[0115]

[0116] The results show that, in the test series, the mixture containing gas black had the lowest crystallization temperature. This confirms that, for other types of gas black, gas black causes the lowest increase in crystallization temperature.

[0117] Implementation Plan 3

[0118] The mixture of the selected above-described embodiments is used as a building material in the selective laser sintering method.

[0119] In experiments not detailed here, it has been demonstrated that the building materials according to the invention can, in principle, be used in conventional laser sintering machines equipped with CO2 laser sources, such as the EOS P396 from EOS Electro Optical Systems, using the standard setup described by the manufacturer. In this experiment, a light source comprising an NIR laser diode was used instead of a CO2 laser. Further details regarding the hardware and suitable setup are provided in European patent application EP14824420.5, published as EP3079912.

[0120] Subsequently, the torsion rate of the obtained component was measured. To quantify the torsion rate, a cube with dimensions of 250 mm × 6 mm × 21 mm was constructed in the rear of the structural space. The manufacturing torsion rate (torsion rate during the manufacturing process) was measured as a percentage of the height difference between the cube's measurement points at its edges and at its center (x = 125 mm), relative to the actual height at the center of the cube, where the height at the center is typically greater than that at the edges.

[0121] As a measure of cooling torsion rate (torsion rate after manufacturing process, which is not formed in missing material compared to manufacturing torsion rate), the curvature of the bottom side of the component at x = 125 mm (the center of the component) is given, wherein the shape of the curved bottom side is approximated by parabolic mathematics.

[0122] Use the following: f(x) = ax 2 And for non-twisted parts, a = 0.

[0123] The curvature of the graph is defined as

[0124] Therefore, at the center of the component corresponding to the vertex of the parabola, κ(0) = 2a.

[0125] The results are shown in Table 3 below.

[0126] Table 3: Measurement of torsion rate of molded articles manufactured from the mixture of embodiments 1 and 2.

[0127]

[0128] The evaluation of the torsion rate test showed that the construction torsion rate of gas black was significantly lower than that of other types of carbon black tested. This confirms the hypothesis that the crystallization temperature of industrial carbon black is related to the torsion rate, i.e., the lower the crystallization temperature, the lower the torsion rate.

[0129] Implementation Scheme Example 4

[0130] In this embodiment, light micrographs of the cooled melt of PA 12 (here, PA 2201) are taken. These images are shown in Figures 2 and 3. Figure 2 shows the cooled melt of PA 12 with large spheroids. Figure 3 PA 12 and industrial carbon black (used) are shown. Cooling fluid of a mixture of PA 12 and fumed black (using Spezialschwarz 4 examples). This type of carbon black acts as a nucleating agent and produces many small spheroids during crystallization. Cooling melt of a mixture of PA 12 and fumed black (using Spezialschwarz 4 examples) is not shown. This type of carbon black does not act as a nucleating agent and does not significantly change the size of the spheroids during crystallization.

[0131] Further results of this experiment are shown in Figure 6-8.

[0132] Implementation Plan 5

[0133] In this embodiment, a mixture of polymer particles and different types of carbon black was prepared. The polymer particles were the same as those used in Embodiment 4. The differences in the types of carbon black lay in the manufacturing method and therefore in their particle size distribution (PSD). As another comparison, mixtures without carbon black types were investigated.

[0134] The DSC isotherms and conversion rates of the blends were recorded, and are exemplarily shown in [the data]. Figure 4 From them, t was determined. 峰 [min] and t 1 / 2 [min] and α [%] conversion rate. t 峰 This refers to the time at which the highest crystallization rate is reached. t 1 / 2 This refers to the time it takes to reach half of the total crystallization. These values ​​are shown in Table 4 below. Figure 5 The distinct crystallization kinetics of the gas black (here: Spezialschwarz 4) are visible via the DSC isotherms and the crystallization conversion curves determined therefrom.

[0135] Table 4:

[0136]

[0137]

Claims

1. A plastic powder used as a building material for additive manufacturing of three-dimensional objects, wherein the three-dimensional object is manufactured by selectively solidifying the building material at locations corresponding to cross-sections in a layer of the three-dimensional object through radiation. The plastic powder comprises a mixture of polymer-based particles and particulate additive particles, and The particulate additive is selected such that the crystallization point of the mixture of the polymer-based particles and the particulate additive increases by no more than 2.5°C compared to the crystallization point of the mixture of the polymer-based particles without the particulate additive, wherein the crystallization point corresponds to T K Initially, measurements were taken using DSC.

2. The plastic powder of claim 1, wherein the particulate carbon material is carbon black and / or graphite, and the carbon black is fumed black.

3. The plastic powder according to claim 1 or 2, wherein the average primary particle diameter of the particulate additive is in the nanometer range.

4. The plastic powder according to claim 3, wherein the particulate additive has an average primary particle diameter of up to 500 nm.

5. The plastic powder according to claim 1 or 2, wherein the particulate additive comprises gas black, the average primary particle diameter of which is 15-70 nm.

6. The plastic powder according to claim 5, wherein the average primary particle diameter of the gas black is 26 nm and a maximum of 58 nm.

7. The plastic powder according to claim 1 or 2, wherein the particulate additive comprises a particulate NIR absorber.

8. The plastic powder of claim 7, wherein the particulate NIR absorber has absorption at at least one of the following wavelengths: 980 nm ± 10 nm and / or 940 nm ± 10 nm and / or 810 nm ± 10 nm and / or 640 nm ± 10 nm.

9. The plastic powder according to claim 1 or 2, wherein it is in the form of a dry mixture of the polymer-based particles and the particulate additive.

10. The plastic powder according to claim 1 or 2, wherein the weight percentage of the particulate additive relative to the total weight of the polymer-based particles and the particulate additive is 0.01%-5%.

11. The plastic powder of claim 10, wherein the particulate additive accounts for at least 0.02% and at most 2% of the total weight of the polymer-based particles and the particulate additive.

12. The plastic powder according to claim 1 or 2, wherein the polymer-based particles comprise at least one polymer selected from at least one of the following as polymer materials: polyaryletherketone, polyarylethersulfone, polyamide, polyester, polyether, polylactide, polyolefin, polystyrene, polyphenylene sulfide, polyvinylidene fluoride, polyphenylene ether, polyimide, polyetherimide, polycarbonate and / or at least one copolymer, comprising at least one of the aforementioned polymers or their monomer units and / or at least one polymer blend, comprising at least one of the mentioned polymers or copolymers.

13. The plastic powder of claim 12, wherein the polymer-based particles comprise amide 12, polyamide 11 and / or polyamide 1012 as polymer materials.

14. The preparation of the plastic powder according to any one of claims 1 to 13, used in a method for additive manufacturing a three-dimensional object by selectively solidifying powdered building materials by radiation at locations corresponding to cross-sections in a respective layer of the three-dimensional object. The preparation described herein includes at least the following steps: (i) providing the polymer-based particles; and (ii) Provide particulate additive particles, and (iii) Dry-mix at least the polymer-based particles and the particulate additive particles.

15. A three-dimensional object, which is manufactured by selectively solidifying a powdered building material based on polymer-based particles and particulate additives by means of radiation at a position corresponding to a cross section in a respective layer of the three-dimensional object, wherein the powdered building material is a plastic powder according to any one of claims 1 to 13. The three-dimensional object said therein has at least one of the following characteristics: (a) A microscopically observable crystalline region in the form of spherules, with a spherule size of at least 20 µm. (b) Twist rate Δ(h) 中心 -h 左 )+ Δ(h 中心 -h 右 The maximum is 0.50mm.

16. The three-dimensional object according to claim 15, wherein the torsion rate Δ(h) 中心 -h 左 )+ Δ(h 中心 -h 右 ≤0.25mm.

17. The three-dimensional object according to claim 16, wherein its torsion rate Δ(h) 中心 -h 左 )+ Δ(h 中心 -h 右 ≤0.20mm.

Citation Information

Patent Citations

  • laser sintering with lasers with a wavelength of 100 to 3000 nm

    DE102004012683A1

  • Producing a three-dimensional object by selectively sintering a polymer powder comprises using a polymer that has a branching group in the main chain, has a modified terminal group and / or has a bulky group in the main chain

    DE102008024281A1

  • Preparing a three-dimensional object from a powder, comprising polymer or copolymer containing an aromatic group that non-linearly links to the main chain, comprises selective sintering of the powder by electromagnetic radiation

    DE102008024288A1

  • Method and material for producing a three-dimensional object by sintering

    DE4410046C1

  • Laser printing system

    EP3079912A1